2021
DOI: 10.3390/v13040712
|View full text |Cite
|
Sign up to set email alerts
|

(E)-Guggulsterone Inhibits Dengue Virus Replication by Upregulating Antiviral Interferon Responses through the Induction of Heme Oxygenase-1 Expression

Abstract: Dengue virus (DENV) infection, which causes dengue fever, dengue hemorrhagic fever, and dengue shock syndrome, is a severe global health problem in tropical and subtropical areas. There is no effective vaccine or drug against DENV infection. Thus, the development of anti-DENV agents is imperative. This study aimed to assess the anti-DENV activity of (E)-guggulsterone using a DENV infectious system. A specific inhibitor targeting signal molecules was used to evaluate the molecular mechanisms of action. Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Isolated guggulsterone, as the major constituent of the C. gileadensis extract, exhibited antiviral activity against Dengue virus (DENV) [ 69 ], herpes simplex virus type 2 (HSV-2), respiratory syncytial virus type B (RSV-B), coxsackie virus B type 3, and adenovirus type 5 [ 70 ]. Guggulsterone was also previously reported in the literature for its potential beneficial effects against COVID-19 disease [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated guggulsterone, as the major constituent of the C. gileadensis extract, exhibited antiviral activity against Dengue virus (DENV) [ 69 ], herpes simplex virus type 2 (HSV-2), respiratory syncytial virus type B (RSV-B), coxsackie virus B type 3, and adenovirus type 5 [ 70 ]. Guggulsterone was also previously reported in the literature for its potential beneficial effects against COVID-19 disease [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the DENV nonstructural protein 5 (NS5) has been shown to interfere with type I IFN signalling by targeting key components of the Janus kinase (JAK)‐signal transducer and STAT pathway, thereby dampening antiviral responses in infected cells 32 . Additionally, the DENV envelope (E) protein can activate the nuclear factor kappa B (NF‐κB) pathway, leading to the production of proinflammatory cytokines and exacerbating neuroinflammation in the CNS 33 …”
Section: Arboviruses and Neurotropic Diseasesmentioning
confidence: 99%
“…Subsequent bio-guided assays revealed that the leaf extract contains guggulsterone as the active compound. Chen et al, (2021) investigated the antiviral activity of guggulsterone against DENV and found that guggulsterone inhibited protein synthesis and RNA replication in DENV in a dose-dependent manner [210]. In vivo analysis in a ICR suckling mouse model demonstrated that guggulsterone stimulates the Nrf2-driven expression of heme oxygenase-1 to increase antiviral interferon response [210].…”
Section: Guggulsteronementioning
confidence: 99%
“…Chen et al, (2021) investigated the antiviral activity of guggulsterone against DENV and found that guggulsterone inhibited protein synthesis and RNA replication in DENV in a dose-dependent manner [210]. In vivo analysis in a ICR suckling mouse model demonstrated that guggulsterone stimulates the Nrf2-driven expression of heme oxygenase-1 to increase antiviral interferon response [210]. Hemeoxygenase-1 is a host antioxidant enzyme that breakdowns the heme ring into biliverdin.…”
Section: Guggulsteronementioning
confidence: 99%